The study on the effects of incentives, work environment, and salary on employee performance in a work from home set-up of a banking company - Castro, Beatrice Mae L. (Animo Repository, 2022)
Due to the COVID-19 pandemic, many employees are advised to work from home which was highly recommended by the government authorities in attempts to control the spread of the virus. Banks in the Philippines is no exception with regards to the notice of implementing a work from home set-up as mandated by the government. This study was conducted with the objective of identifying the relationship of incentives, work environment, and salary with employee performance and determine the impact of the three independent variables on the employee dependent variable. This research was conducted to a whole department of a bank in the Philippines where it had 33 employees. The researchers was also able to determine the effect of having a work from home set-up in the incentives, work environment, and salary of the employees. The results showed that there were little to no additional incentives that were given, no changes in the salary, and various changes in the work environment, can either have positive or negative effect. To carry out this objective, a simple and multiple linear regression was utilized which yielded a significant and positive relationship among the said variables. Determining variables that plays a role in the performance of the employee gives companies and its managers the chance to analyze how to improve that aspect and contribute to the overall success of the company.